Lung transplantation in patients with incidental early stage lung cancer—institutional experience of a high volume center. Issue 8 (16th June 2016) - Klikovits, Thomas; Lambers, Christopher; Ghanim, Bahil; Dome, Balazs; Murakoezy, Gabriella; Zöchbauer‐Müller, Sabine; Waseda, Ryuichi; Aigner, Clemens; Lang, Gyoergy; Taghavi, Shahrokh; Klepetko, Walter; Jaksch, Peter; et al.
Abstract: Background: Incidentally discovered lung cancers in lung transplant (LuTX) recipients are rare but may affect outcome. We aim to report our single center experience with incidence, management, and survival of patients with previously unverified primary lung cancer discovered at the time of LuTX. Methods: A total of 1262 patients undergoing LuTX between 1989 and 2012 were retrospectively analyzed in our prospective database. Results: Patients identified were six men and five women with a mean age of 54.4±9.9 years. The indication for LuTX was COPD (n=9), pulmonary fibrosis (n=1), and cystic fibrosis (n=1). Histological diagnosis of the explanted lung revealed adenocarcinoma in six, squamous cell carcinoma in three, and lepidic predominant adenocarcinoma in two cases, respectively. Staging revealed stage IA (pT1a/b pN0) in eight and IB (pT2a pN0) in two cases and one patient in stage IIA (pT1b pN1). Subsequent cancer staging after LuTX revealed no metastasis. Immunosuppression was adjusted and no adjuvant chemo‐ or radiotherapy was administered. The 5‐year survival rate was 90.5% with no detection of recurrence. Conclusion: In patients with incidentally detected early stage lung cancer at the time of LuTX, rates of recurrence and survival based on this sample appear to be acceptable.